Beckman ebook - Burrowes, Grace (Lonely Lords, 2013)
Beckman Haddonfield is ready to live again... Beckman finally emerges from the shadow of his wife's death by agreeing to restore a family estate...and embarking on a dalliance with the quiet, mysterious housekeeper who resides there. But she is not who she seems... Riveting and refreshing, Beckman is an unforgettable story about love's power to overcome grief and guilt. Award-winning New York Times and USA Today bestselling author Grace Burrowes's gorgeous writing and lush Regency world will stay with you long after you turn the final page.